The quality of clinical diagnosis and procedure coding and risk factors for malnutrition among hospitalized geriatrics in Hospital Universiti Sains Malaysia - Sahran, Nur-Fazimah (2015)
Malnutrition is highly prevalent among hospitalized geriatrics. Unfortunately, the identification, notification and clinical coding of malnutrition have been reported to be inadequate. In order to place malnutrition in the focus of the healthcare system, it is mandatory to assess the current practice and the quality coding for malnutrition to improve the overall quality in healthcare services. Therefore, the objectives of this study were; (1) to determine factors associated with malnutrition among hospitalized geriatrics (2) to study the impacts of malnutrition on clinical outcomes (3) to explore the completeness documentation of nutritional information and (4) to identify the causes of coding issue for malnutrition. A cross-sectional study was conducted among hospitalized geriatrics aged 60 years and above in Hospital USM. A total 130 participants were recruited in this study consists of 49 (37.7%) men and 81 (62.3%) women. The nutritional assessments conducted were anthropometric measurement and biochemical assessment coupled with standard nutritional screening and assessment tools. A systematic reviewed on the medical records for nutritional information and clinical coding was conducted once participant was discharged. Data were analysed using SPSS version 20. Results revealed that 35.4% of participants were malnourished according to standard reference Subjective Global Assessment (SGA). Multivariate analysis demonstrated that malnutrition were significantly associated with low BMI (p<0.001) and albumin (p<0.05), loss of appetite (p<0.001) and surgical procedure (p<0.05). Malnourished geriatrics were found to have significantly longer hospital stay, higher complication and readmission rate compared to well-nourished geriatrics (p<0.05). The documentation of weight was 48.5%, height; 27.7%, weight loss; 3.1%, dietary intake; 43%, loss of appetite; 11.5% and digestion problem; 32.3%. Only 50% of malnourished were intervened. None of the participants had been diagnosed and coded with malnutrition. The causes of coding issue for malnutrition were; lack of awareness among healthcare professional (50.0%) and incomplete medical documentation (50%) at the ward level. In addition, two causes were occurred for diagnosis and procedure coding; uncoded (52.2%), miscoding diagnosis (39.1%), missing diagnosis code (8.7%), missing procedure codes (26.7%), and unavailable codes for dietary counselling and oral nutritional supplementation (73.3%). In conclusion, the quality of clinical coding of malnutrition is mooted to be improve. Structured assessment and standard documentation of malnutrition will allow optimization of this information to be used in improving patient care management and quality of healthcare services